(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor impairments due to dopamine deficiency. Safinamide mesylate, a selective monoamine oxidase-B (MAO-B) inhibitor with additional glutamate-modulating properties, is used as an adjunct therapy to reduce motor fluctuations in PD patients. However, its short half-life and limited absorption in the upper gastrointestinal tract necessitate frequent dosing, leading to fluctuating plasma drug levels and reduced patient adherence. To address these challenges, this study focuses on the formulation and evaluation of floating microcapsules of Safinamide mesylate to achieve sustained drug release and prolonged gastric retention. Floating microcapsules were prepared using the solvent evaporation method with polymers such as hydroxypropyl methylcellulose (HPMC), ethyl cellulose, and Eudragit to ensure buoyancy and controlled drug release. The prepared microcapsules were characterized for particle size, entrapment efficiency, in vitro floating behavior, and drug release kinetics. The results demonstrated excellent buoyancy and sustained drug release over an extended period, potentially maintaining stable plasma concentrations and enhancing therapeutic efficacy. This gastroretentive drug delivery system offers a promising approach to improving the bioavailability and patient compliance of Safinamide mesylate in PD management. Further in vivo studies are required to validate its clinical effectiveness and establish its potential as an optimized treatment strategy for Parkinson’s disease.